Incidence of environmental business policies in the management of solid waste in the construction sector, Lima 2018 - Mendiola Lázaro de Ortecho, Alberto (2020)
A problem of the big cities and, therefore, of Lima, is the damage to the environment because the solid residues generated by construction activities. The present study seeks to demonstrate that a good and comprehensive solid waste management can be done through the application of effective environmental business policies, with rules and regulations, and not simple statements of good intention. The means of measurement is a questionnaire captured in a survey of 86 professionals from the construction sector in Lima, and which results have produced two types of analysis: one statistical that demonstrated the significant positive correlation (incidence) between the two variables, and the other one with contributions from the interviewees for good, comprehensive solid waste management in the jobsite.